(untitled) (Plant Tissue Culture and Biotechnology, 2020)
Plant extracts were evaluated on bacteria isolated from poultry farm for developing substitutive therapeutic agent of antibiotics. A diverse range of bacterial load observed both in total viable count (TVC) and in total coliform count (TCC) in 30 samples randomly collected from poultry feeds, drinking water and faeces. A total of six bacterial isolates e.g. Pseudomonas spp., Aeromonas spp., Citrobacter spp., Vibrio spp., Escherichia coli and Plesiomonas spp. were found in the samples cultured in MacConkey Agar medium. Fifteen antibiotics were studied against bacterial susceptibility. All the bacterial isolates exhibited multi-antibiotic resistance (MAR) with gross resistance to erythromycin and ampicillin. E. coli had the highest MAR (53.3%), and Vibrio spp. as well as Plesiomonas spp. both had the same MAR (46.7%). Methanolic extract of Terminalia chebula and Azadirachta indica showed significant zone of inhibition against all the tested bacteria. These findings confirm the presence of multidrug resistant bacteria in poultry environment that reveals a possibility of cross-contamination to human and animals. The plant extracts could be developed into therapeutic drugs to rein antibiotic poultry resistant bacteria. Plant Tissue Cult. & Biotech. 30(1): 119-130, 2020 (June)